Peran Pengawasan Kepala Madrasah dalam Meningkatkan Kualitas Pembelajaran di MA NW Pengkelak Mas: The Role of Madrasah Principal Supervision in Improving the Quality of Learning at MA NW Pengkelak Mas - Sirajun Nasihin; Ozi Satria; Anggun Era Sntika; Aqis Mawaddah; Baiq Ismi Azizah (Al-Gafari : Manajemen dan Pendidikan, 2026)
This study aims to describe the role of the principal's supervision in improving the quality of learning at MA NW Pengkelak Mas. The focus of this study is to determine the form of supervision carried out by the principal and its impact on learning activities. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through interviews, observation, and documentation. The results of this study indicate that the principal plays an active role in implementing supervision through classroom supervision, evaluation of learning tools, and professional development of teachers. This supervision has a positive impact on increasing teacher discipline, orderly learning administration, and the development of a variety of learning methods and strategies applied by teachers. In addition, communicative and fostering supervision helps create a harmonious working relationship between the principal and teachers. Thus, supervision that is carried out routinely, directed, and sustainable makes a real contribution to improving the quality of learning at MA NW Pengkelak Mas.